Karakteristik dan Kualitas Nata De Cane dari Nira Tebu (Saccharum officinarum L.) dengan Penambahan Ekstrak Kedelai (Glycine max L.) sebagai Sumber Nitrogen - Wigiyanti, Vitriya; Zakiah, Zulfa; Rahmawati, Rahmawati (Bioma : Berkala Ilmiah Biologi, 2023)
Sugarcane sap is a liquid found in sugarcane stalks, which can be drunk directly as a refreshment and as a basic ingredient for making granulated sugar. The nutritional content contained in sugarcane juice can be a growth medium for Acetobacter xylinum bacteria forming cellulose (nata). One of the factors supporting the growth of Acetobacter xylinum bacteria is a nitrogen source. This study aims to determine the effect and the best concentration of soybean extract on the quality characteristics of nata de cane. The research design used was a completely randomized design (CRD) with 7 concentrations of nitrogen sources including control (0%), 1% ZA, 2.5%, 5%, 7.5%, 10% and 12.5% soybean extract. Each treatment consisted of 4 replications. Parameters observed were the thickness and fiber content of nata and then analyzed using ANOVA (Analysis of Variance). Based on the results of the study, the addition of soybean extract (Glycine max L.) had an effect on the thickness and fiber content of nata de cane compared to the control treatment. The resulting Nata has a chewy texture and a distinctive aroma of fragrant sugarcane juice. The highest thickness and fiber content of nata de cane was obtained in the 12.5% soybean extract treatment, namely 1.58 cm and 2.95% and has met the quality requirements of SNI 01-4317-1996. Overall, the most preferred nata de cane organoleptic test result was nata de cane with the addition of soybean extract at a concentration of 12.5% in the very like category. The reseach results can be recommended to the public that soybean extract has the potential as an alternative to ZA in the process of making nata.